Distinctions between Fournier's gangrene and lower extremity necrotising fasciitis: microbiology and factors affecting mortality. (September 2022) - He, Xuefeng; Xiang, Xin; Zou, Yong; Liu, Bing; Liu, Lili; Bi, Yaodan; Kan, Daohong
Highlights: Aetiology variated upon the infected region for necrotising fasciitis (NF). Gram-negative bacteria emerged as a common pathogen for monomicrobial NF. High Fournier's gangrene (FG) severity index score (greater than 7) was strongly correlated with poor outcomes for FG. Sepsis at admission was an alarming indicator of poor outcomes for lower extremity NF. Abstract: Objectives: In this study, we aimed to illustrate distinctions between Fournier's gangrene (FG) and lower extremity necrotising fasciitis (NF) and screen out possible risk factors of poor prognosis for each cohort. Methods: The medical records of qualified patients with NF admitted to the Second People's Hospital of Yibin from January 2016 to June 2021 were retrospectively reviewed. All participants were anatomically categorised into FG and lower extremity NF groups, and their baseline data and microbiological results were compared. Further comparisons of critical parameters were conducted between survivors and nonsurvivors within each group. Results: A total of 49 patients were included in the study with a median age of 58 years, and overall mortality was 20.4%. There were 18 patients with FG and 31 patients with lower extremity NF. A microbiology distinction was found—the predominance of gram-negative infection in FG and gram-positive infection in lower extremity NF. High Fournier's gangrene severity index scores (greater than 7), advanced age, procalcitonin and D-dimer value were identified as risk factors for FG, and the presentation of sepsis was an alarming indicator for lower extremity NF. Conclusions: The distinction of microbiology might provide advice for appropriate antibacterial administrations. In addition, with practical prognostic predicting tools, clinicians might be able to identify patients at increased risk and intervene promptly to avoid unfavourable outcomes.